Fiscal Policy and Work Incentives – An International Comparison - Pressman, Steven (Journal of Income Distribution®, 2002)
This paper uses the Luxembourg Income Study to examine the tradeoff between government redistribution of income and efficiency in the labor markets over time and across countries. Poverty rates using factor incomes are similar and stable for 9 developed countries over 15 years; but after government fiscal policies, disposable income poverty rates vary considerably. Simple regressions of government redistribution efforts and labor force participation rates show a small effect of redistribution on labor force participation – every time fiscal policy helps to bring 1 percent of the pre-fisc poor above the poverty line, labor force participation rates decline by .2 percentage point. Multiple regression models that control for other determinants of labor force participation give similar results.